ANALISIS STRATEGI DINAS KESEHATAN KOTA SEMARANG DALAM PENYELENGGARAAN PELAYANAN KESEHATAN ORANG DENGAN RISIKO TERINFEKSI HIV - Kaminang, Megawati Ayu Zharani; Jati, Sutopo Patria; Fatmasari, Eka Yunila (Jurnal Kesehatan Masyarakat (e-Journal), 2019)
Target for achievement data of the minimal operational standart for 2017 in Semarang City Health Services for People with an HIV risk is 89.55%. Meanwhile, the number of HIV casses in Semarang City in the last three years continues to increase. The aim of the researchers was to describe the strategy of the Semarang City Health Service in administering health services for people at risk of HIV infection. The research is qualitative study with a descriptive method. The main informants were the holders of HIV programs in Semarang Health Office, with triangulation that is HIV program holders in Bandarharjo and Lebdosari Puskesmas, program and monitoring-evaluation holders of Semarang Aids Prevention Commission. The results of the study found that the internal factors is an illustration of the strengths and weaknesses of the Semarang Health Office. Strengths and weaknesses possessed by Semarang Health Office namely marketing and promotion that have been carried out by utilizing technology, human resources for these services have already received training, financial resources have been provided through the APBD and APBD and production-operation activities already exist in the Semarang City. External factors as an illustration of the opportunities and threats of the Semarang Health Office, namely partners already owned by the Semarang Health Office in supporting this program, demographic environment, economic and political environment and law. The results of the situation analysis led the Semarang Health Office to be in an "aggressive" position in strategy quadrant which indicates that the organization has strengths and opportunities where these advantages in supporting organizational policies grow more aggressively. The alternative strategy that can be applied by the Semarang Health Office is to improve acces and facilities for HIV services in Semarang city.